Activation of embryogenic cell division in leaf protoplast-derived alfalfa cells: the role of auxin and stress - Fehér, Attila; Pasternak, Taras; Dudits, Dénes (Acta Biologica Szegediensis, 2002)
Leaf protoplast-derive d cells of the embryogenic alfalfa genotype (Medicago sativa ssp. varia A2) follow different fate if cultured in the presence of 0.25, 1 or 10 uM 2,4 - dichlorophenoxyacetic acid (2,4-D). Cells grow n in the presence of the highest auxin (2,4-D) concentration become embryogenic and can develop into somatic embryos if subcultured into fresh medium with the lower 2,4- D level. Cells cultured at the lower auxin concentrations from the beginning develop into elongated differentiated cells. In order to reveal physiological changes that characterize the reactivation of cell division in resting cells as well as the transition of somatic plant cells to an embryogenic state, morphological, cell division, intracellular pH and stress-related parameters have been determined during the first five days of parallel cultures at the above 2,4-D concentrations in combination with stress treatments.